FACILITATING PROBLEM BASED LEARNING THROUGH E-PORTOFOLIOS IN EFL - Veneranda Hajrulla (European Scientific Journal, ESJ, 2014)
The use of electronic portfolios, or e-portfolios, is considered an emerging practice in preservice teacher education. The twenty-first century is an attempting time for teachers. Traditional ways of teaching, are no longer adequate to prepare our new generation for the knowledge based economy. The challenge now, for foreign language trainers, is to equip students with learning, critical thinking, and problem-solving skills that will enable them to cope with the demands of this fast moving environment. Problems make us think and we learn by thinking. Languages are learnt more effectively when we use them to solve problems. This chapter describes the development of an e-portfolio to support the problem-based learning process, with the aim of using it to scaffold knowledge construction, document students' learning, and facilitate evaluation. Exactly the use of an eportfolio in a course of English Language Teaching module, for student teachers in Albania.